AHP-TOPSIS-based analysis for the wettability of agro-industrial waste particulates Bhimal fiber-reinforced epoxy bio-composites in different oil water environments - Deepak Gupta; Arun Kumar Chaudhary; Deepak Verma; Warshi Singh; Senthilkumar Nangan; Sundaram Thanigaivel; Saravanan Rajendran; Maximilian Lackner (Green Chemistry Letters and Reviews)
The work studied the use of agro-industrial untreated waste for bio-composites as a sustainable material and determined its wettability in diverse environments. To prepare the bio-composites, Bhimal natural fiber was compositely reinforced with CaCO3 composite platelets and Flyash along with TiO2 at different concentrations (5%, 10%, and15% by weight) into an epoxy matrix. The samples were tested in petrol, diesel; kerosene, seawater Ganga water; rainwater, and distilled water at 168 hours and the saturation was stabilized after measuring every 48 h. The absorption resistance, especially in oil-based environments was excellent in TiO2 15%-based bio-composites. Materials were ranked by the Analytic Hierarchy Process (AHP) and TOPSIS methods. The results show the potential of TiO2 composites for low wettability applications without any chemicals as well, which may encourage green materials from agro-industrial waste.